2018
DOI: 10.1016/j.biomaterials.2018.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Development and MPI tracking of novel hypoxia-targeted theranostic exosomes

Abstract: Treating the hypoxic region of the tumor remains a significant challenge. The goals of this study are to develop an exosome platform that can target regions of tumor hypoxia and that can be monitored in vivo using magnetic particle imaging (MPI). Four types of exosomes (generated under hypoxic or normoxic conditions, and with or without exposure to X-ray radiation) were isolated from MDA-MB-231 human breast cancer cells. Exosomes were labeled by DiO, a fluorescent lipophilic tracer, to quantify their uptake by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
151
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 61 publications
0
151
0
Order By: Relevance
“…An interesting example of active loading of probes is the use of transporter proteins on the membrane of exosomes. A study reported the encapsulation of glucose-coated gold nanoparticles by the GLUT1 glucose transporter on the exosomal membrane [75]. Additional transporters are expected to be available for the specific encapsulation of probes in exosomes obtained from different sources with the advancement of research.…”
Section: Labeling Methodsmentioning
confidence: 99%
“…An interesting example of active loading of probes is the use of transporter proteins on the membrane of exosomes. A study reported the encapsulation of glucose-coated gold nanoparticles by the GLUT1 glucose transporter on the exosomal membrane [75]. Additional transporters are expected to be available for the specific encapsulation of probes in exosomes obtained from different sources with the advancement of research.…”
Section: Labeling Methodsmentioning
confidence: 99%
“…Different cells under different conditions determine the heterogeneity of EVs, and different cell-derived EVs may be home to specific tissues (Thery et al, 1999;Colombo et al, 2014). For instance, EVs derived from hypoxic tumor cells tend to be taken up by hypoxic tumor cells (Jung et al, 2018). Again, central nervous system-derived EVs can cross the BBB and serve as a unique DDS for specific neuron populations .…”
Section: Cell Targeting Propertiesmentioning
confidence: 99%
“…As 'molecule carrier', EVs may serve as novel tools for various therapeutic and diagnostic purpose (EL Andaloussi et al, 2013;Ohno et al, 2016), such as anti-tumor therapy (Poggio et al, 2019), immune-modulatory (Buzas et al, 2014), and drug delivery (Gudbergsson et al, 2019). As a drug delivery vesicle, EVs have been tested for the delivery of siRNAs (El-Andaloussi et al, 2012), miRNAs (Li et al, 2019c), proteins (Haney et al, 2015), small molecule drugs (Zhuang et al, 2011), nanoparticles (Jung et al, 2018), and CRISPR/Cas9 into animal models. Owing to their natural origin, EVs are born with high biocompatibility, enhanced stability, and limited immunogenicity, which provide potential advantages over traditional synthetic delivery vehicles, such as liposomes and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Before this, EV imaging and tracking methods can serve as a guide to direct the development, optimization, and implementation of EV-based therapeutics. To date, considerable effort has been devoted to develop EV tracking methods using fluorescence imaging (14,15), bioluminescence imaging (16), single-photon emission computed tomography (SPECT) (17), positron emission tomography (PET) (18), computed tomography (CT) (19,20), magnetic resonance imaging (MRI) (21,22), and magnetic particle imaging (23). Among them, MRI is an appealing imaging modality that is used widely in the clinic and has excellent soft-tissue contrast without using ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%